2023
DOI: 10.3389/fmicb.2023.1208816
|View full text |Cite
|
Sign up to set email alerts
|

Microbial signature of intestine in children with allergic rhinitis

Abstract: IntroductionPrevious studies have found that unique patterns of gut microbial colonization in infancy associated with the development of allergic diseases. However, there is no research on the gut microbiota characteristics of AR children in Chinese Mainland.ObjectiveTo investigate the changes of gut microbial of AR children in Chinese Mainland and evaluate the correlation between gut microbial and clinical indexes.MethodsIn this clinical study, fecal samples from 24 AR children and 25 healthy control children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…A reduction in Firmicutes coupled with an increase in Bacteroidetes results in diminished production of SCFAs. This may enhance intestinal permeability, thereby triggering an inflammatory response and potentially elevating the risk of allergic conditions (Yamaguchi et al, 2023;Zhang P. et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in Firmicutes coupled with an increase in Bacteroidetes results in diminished production of SCFAs. This may enhance intestinal permeability, thereby triggering an inflammatory response and potentially elevating the risk of allergic conditions (Yamaguchi et al, 2023;Zhang P. et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study in Ecuador showed that increased fecal abundance of Streptococcus and Bacteroidetes and decreased abundance of Bifidobacterium and Ruminococcus in children as young as 3 months old was associated with allergy and wheezing at age 5 years ( 88 ). Research by Zhang et al showed that the diversity of gut microbial in children with AR was reduced and the abundance of Bacteroidetes was significantly increased, and changes in the gut microbial were correlated with clinical symptoms ( 89 ). The gut microbiota plays a crucial role in the immune system by influencing the development of either responsive or tolerant reactions to various antigens.…”
Section: Common Risk Factors For Allergy and Tdmentioning
confidence: 99%